COMPARATIVE EVALUATION OF PHYSICAL CHARACTERISTICS OF MITHUN (Bos frontalis) (Indian Journal of Animal Production and Management, 2015)
The study on physical characteristics was carried on 20 Mithuns irrespective of sexes, 5 from each strain collected from the States of Arunachal Pradesh (AR), Mizoram (MZ), Manipur (MN) and Nagaland (NL). The value for head breadth was significantly (P< 0.05) higher in MN strain and the least in MZ strain of mithun. The values for muzzle circumference, wither height, pouch girth, fore shank length, cannon circumference, thigh length, tail length, tail circumference and body weight were significantly (P< 0.05) higher in AR strain as compared to other strains of mithun. The values for height at naval and pouch points were significantly (P< 0.05) higher in NL and the lowest in AR strain. The values for physical characters like length of head, horn, ear, neck, barrel, croup, fore arm and hind shank and their circumferences, eye to eye space, rump height, heart girth, abdominal girth and the heights at sterna did not vary significantly amongst four strains of mithun. It can be concluded that AR strains of mithuns have better body conformation as compared to other strains of mithun. Further, all the strains of mithun had almost similar body conformation like other bovines; however, such study should be repeated with large sized samples keeping the present investigation as a base-line work.
Keywords: Body conformation; Physical characteristics; Mithun